Performance evaluation of Cohen-Coon and Ziegler-Nichols PID tuning methods in liquid flow control system / Muhammad Haziq Firdaus Mohd Kamil - Mohd Kamil, Muhammad Haziq Firdaus (2024)
This study discusses the method to optimise liquid flow process control by using efficient Proportional-Integral-Derivative (PID) tuning values. In order to achieve that, this study explores the application of Cohen-Coon and Ziegler-Nichols tuning method, which the main character for obtaining desired control outcomes. An evaluation of the effectiveness of proportional (P), proportional and integral (PI), and proportional plus integral and derivative (PID) tuning parameters is conducted using a Liquid Flow Process Control Training System (Model: SE113). The Cohen-Coon method is known in handling processes with significant dead time (Td), providing a balanced approach between speed and stability [3] [9]. Besides, Ziegler-Nichols method is a foundational method for tuning PID controllers, widely used in industrial control systems. The response curve is used to extract the process response characteristics, such as Response Rate (RR), Dead Time (Td), and Constant Time (Tc), which are necessary for accurate controller tuning. The process responses obtained are used to calculate tuning parameters using the Cohen-Coon and Ziegler-Nichols tuning method. By comparing both tuning methods, this study aims to focus on their respective strengths and limitations in liquid flow control applications and recommend the most appropriate method that able to achieve the best performance for liquid flow control system.